Política nacional de resíduos sólidos: o poder transformador e integrador da gestão jurídica dos resíduos sólidos - Emilio, Patricia Raysel (2014)
In August 2, 2010, was promulgated the law that instituted the National Policy on Solid Waste with its principles, objectives and instruments which proposes to solve or at least minimize the problems of solid waste. The garbage was treated in the Law of Nacional Policy on Solid Waste as solid waste, juridical object amenable to management. Under the law ,the integrated management regulates the whole product life cycle and aims to achieve sustainable patterns of production and consumption, in addition to the environmentally appropriate disposal. To do this, each participant of the steps in the chain of waste generation will be held responsible for your obligational part including the final consumer, different that occurs before the Law of National Policy on Solid Waste when solid wastes were managed only after the disposal, by the holder of public cleaning. The reclaimable and recyclable solid waste becomes a social value economic, this change of paradigm proposed by the Law of National Policy on Solid Waste makes environmental education indispensable to changing values, behaviour and lifestyle of society. If not intended, no time, to produce a manual of solid waste or about, just highlight the transformation proposed by law of National Policy on Solid Waste in relation to management of solid waste